Learner's attitudes, perceptions and efforts towards mandarin as a foreign language course - See Soo Yin; Arifuddin Abdullah (2014)
This paper examines the attitudes and perceptions of learners towards learning Mandarin language as a foreign language course at a local public university in Malaysia. In Malaysia, Mandarin language course is offered to foreign language students either as a compulsory elective or free elective course at university level. Nevertheless, majority of the students are still unable to communicate well in the language upon completion of the course. This quantitative field research employs questionnaires and purposive sampling technique as the methods of collecting data. The sampling involves 74 students from Universiti Malaysia Kelantan (UMK) Jeli Campus who enrolled in Level 2 Mandarin course. While the paper discusses learners‟ attitudes it also highlights their perceptions towards Mandarin language learning environment and their efforts to enhance the mastery of Mandarin during the learning period. The findings revealed that majority of the respondents seemed to show positive attitudes towards Mandarin, such as their willingness to promote the course to their friends and determination to continue to learn the language after graduation. However, majority of the students were also found to have feelings of anxieties while learning Mandarin. Thus, the anxiousness arose during the language class has no apparent effect on their language learning as they claimed. As a whole, this research suggests that language instructors should seek ways to motivate the students to improve their speaking skills especially through group learning strategies.